2020
DOI: 10.1101/2020.07.16.203497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regeneration of Functional Retinal Ganglion Cells by Neuronal Identity Reprogramming

Abstract: Degeneration of retinal ganglion cells (RGCs) and their axons underlies vision loss in glaucoma and various optic neuropathies. There are currently no treatments available to restore lost vision in patients affected by these diseases. Regenerating RGCs and reconnecting the retina to the brain represent an ideal therapeutic strategy; however, mammals do not have a reservoir of retinal stem/progenitor cells poised to produce new neurons in adulthood. Here, we regenerated RGCs in adult mice by direct lineage repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Second, the newly generated neurons were reported to be morphologically, functionally, and molecularly indistinguishable from wild-type neurons in some studies (6-10) but abnormal and immature in others (3)(4)(5). Third, three studies reported that newly generated RGCs rapidly extended axons through the optic nerve to synapse on central targets and mediate visually evoked behaviors (7,8,10), despite the fact that regeneration of axotomized RGCs is highly inefficient in adult mammalian retina and the very limited number of regenerating axons seldom reach central targets (11).…”
Section: Interpreting Divergent Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the newly generated neurons were reported to be morphologically, functionally, and molecularly indistinguishable from wild-type neurons in some studies (6-10) but abnormal and immature in others (3)(4)(5). Third, three studies reported that newly generated RGCs rapidly extended axons through the optic nerve to synapse on central targets and mediate visually evoked behaviors (7,8,10), despite the fact that regeneration of axotomized RGCs is highly inefficient in adult mammalian retina and the very limited number of regenerating axons seldom reach central targets (11).…”
Section: Interpreting Divergent Resultsmentioning
confidence: 99%
“…Put simply, the ability to generate photoreceptors or RGCs from endogenous MG would be far more useful than the ability to generate amacrine and bipolar cells. Cre-expressing transgenic lines used to restrict expression in other studies (3)(4)(5)10) are subject to similar caveats regarding specificity of expression. In these cases, however, the cell-type specificity of the transgenes had been rigorously established in previous studies, and scRNA-Seq analysis was used to demonstrate the presence of bipolar and amacrine-like precursors.…”
Section: Interpreting Divergent Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could possibly explained by Müller cells conversion to RGCs converted, as a response to ischemic insult, and also expressed Brn3a. Wei et al ( 18 ) previously showed that retinal neuronal identity switching, triggered migration of amacrine interneurons from the inner nuclear layer to the RGCs layer which may imply that neurons exhibit surprisingly unexpected plasticity, which could result in regenerative manifestations.…”
Section: Discussionmentioning
confidence: 99%